ANALISIS EFISIENSI UNIT PENANGKAPAN PUKAT CINCIN DI PELABUHAN PERIKANAN PANTAI LAMPULO BANDA ACEH - Aprilia, Ratna Mutia; Mustaruddin, Mustaruddin; Wiyono, Eko Sri; Zulbainarni, Nimmi (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Measurement of productivity, technical and economic efficiency are the key indicators in assessing the ability of purse seine fishing unit based in Fishing Port Lampulo, Banda Aceh. The objectives of this study are to analyse of productivity and effeciency of purse seine units. There were some factors that support the production catches of purse seine fishing unit such as the size of the vessel, engine power, length of nets, net height, number of crew, fuel, number of light, the amount of ice, freshwater and supply costs were analyzed using the Cobb-Douglas approach. Productivitiy calculation had done by using the approach of purse seine catches for the year divided by amount of Gross Tonnage and catching trip. The results showed the highest productivity per trip was 1.86 tons/trip in 2012 and the highest productivity per GT was 9.97 tons/GT in 2011. Production factors which significantly affect to catch of purse seine were engine power, net height, number of crew, number of lights and supply cost. Analysis of the technical efficiency towards 54 vessel showed that the vessel engines power production factors (-0.432), the number of crew (-1.116), and number of lights (-0.148) the value of its production elasticity were inefficient (Ep <0), whereas purse seine net height (0.467) was at the rational production stage (0<Ep<1) and factor costs of production supplies (2.181) was efficient (Ep>1) which means inefficient use of production factor. Economic efficiency for the use of production factor wass inefficient because the value of NPMxi/PXI<1.